Cybersecurity and its impact on risk management facing tourism organizations – A case study at Baghdad international airport - Maktouf, Muhammad Abd; Alobaidi, Muthanna (Edelweiss Applied Science and Technology, 2025)
The research aimed to test the impact of Cybersecurity and its dimensions (Political, Economic, Information Protection, Legal, Military, Academic, Educational) in improving Risk Management among Baghdad airport managers. The total community size was 87, and the random research sample was selected using the model (D. MORGIN). A total of 71 questionnaires were distributed, and according to the results, 67 questionnaires were retrieved, all of which were valid for statistical analysis. The program (SPSS v.28) was used to analyze the answers of the sample members. The data were collected, analyzed, and the validity and stability of the study tool were confirmed using parametric statistical methods (Alpha Cronbach) to determine internal consistency for all elements. Percentage and frequency tables were created using the answers of study sample members regarding personal information such as gender, age, educational qualification, and number of years of service. Correlation and regression, mean and standard deviation, and the (T) test for the difference between variables (Independent Sample T Test) were used with Pearson techniques for statistical analysis of data at the level of significance ∂≤0.5. The results indicated that the availability of cybersecurity and its dimensions was high, while risk management and its dimensions were available moderately. Additionally, the impact of cybersecurity and its dimensions on risk management was noted.